2018
DOI: 10.1111/bph.14347
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoke up‐regulates PDE3 and PDE4 to decrease cAMP in airway cells

Abstract: Background and PurposecAMP is a central second messenger that broadly regulates cell function and can underpin pathophysiology. In chronic obstructive pulmonary disease, a lung disease primarily provoked by cigarette smoke (CS), the activation of cAMP‐dependent pathways, via inhibition of hydrolyzing PDEs, is a major therapeutic strategy. Mechanisms that disrupt cAMP signalling in airway cells, in particular regulation of endogenous PDEs, are poorly understood.Experimental ApproachWe used a novel Förster reson… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 67 publications
1
26
0
Order By: Relevance
“…This is consistent with the findings of in vitro experiments showing that ASM human cells are primarily sensitive to cilostamid (PDE3 inhibitor), while both ASM cells and human non-polarized bronchial epithelial (16HBE 14o) cells are responding to PDE4 inhibition by roflumilast. Moreover, selective PDE4 inhibition was found to induce an effective reversion in the CBF down-regulation induced by cigarette exposure in ex vivo conditions under which expression of both PDE3 and PDE4 enzymes is dominant (Milara et al, 2012;Zuo et al, 2018). Furthermore, LABA enables roflumilast (selective PDE4 inhibitor) ability to stimulate CBF in cigarette smoke exposed cells, while roflumilast itself does it only in limited manner, as demonstrated by Schmid et al (2015).…”
Section: Selective Pde4 Inhibitorsmentioning
confidence: 96%
See 1 more Smart Citation
“…This is consistent with the findings of in vitro experiments showing that ASM human cells are primarily sensitive to cilostamid (PDE3 inhibitor), while both ASM cells and human non-polarized bronchial epithelial (16HBE 14o) cells are responding to PDE4 inhibition by roflumilast. Moreover, selective PDE4 inhibition was found to induce an effective reversion in the CBF down-regulation induced by cigarette exposure in ex vivo conditions under which expression of both PDE3 and PDE4 enzymes is dominant (Milara et al, 2012;Zuo et al, 2018). Furthermore, LABA enables roflumilast (selective PDE4 inhibitor) ability to stimulate CBF in cigarette smoke exposed cells, while roflumilast itself does it only in limited manner, as demonstrated by Schmid et al (2015).…”
Section: Selective Pde4 Inhibitorsmentioning
confidence: 96%
“…At present, there are no specific therapies available to correct the ciliary dysfunction and the empiric treatment helps only to manage the consequences of dysfunctional cilia. Therefore, inhalational route of administration and focusing on mechanisms ameliorating the ciliary beating frequency (e.g., increased intracellular concentrations of cyclic nucleotides caused by PDE inhibition) might be of huge benefit (Milara et al, 2012;Kogiso et al, 2018;Zuo et al, 2018).…”
Section: Pde/pde Inhibitors and Copdmentioning
confidence: 99%
“…Interestingly, it has been shown that ultrafine particulate matter initiates the process of EMT in BEAS-2B cells (Thevenot et al, 2013)-a process accompanied by a loss of E-cadherin and a gain in α-SMA. Recent studies reported on alterations of the expression of the AKAP member: AKAP5, AKAP12, ezrin and AKAP9 in experimental models of COPD (Oldenburger, Poppinga, et al, 2014;Poppinga et al, 2015), next to a change in the expression of Epacs and PDEs (Oldenburger, Timens, et al, 2014;Zuo et al, 2018), clearly indicating that oxidative stress alters the subcellular composition of cAMP scaffolds. Therefore, future studies should aim to target cAMP scaffolds either by stabilizing their composition or modifying their composition.…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been reported that PDE1-PDE8 subtypes are highly expressed in lung epithelial cells (Fuhrmann et al, 1999;Haddad et al, 2002;Page & Spina, 2012;Zuo et al, 2018), the precise role of the distinct PDEs in the diverse functions of epithelial cells is still unclear. In A549 cells, TGF-β1 treatment resulted in a significant increase in gene expression of PDE4A, PDE4D, and PDE8A, whereas the gene expression of PDE1A, PDE3A, and PDE7B was decreased (Kolosionek et al, 2009).…”
Section: The Role Of Pde Family Members In Emtmentioning
confidence: 99%
“…There are 11 families and 30 subtypes of PDE in humans, of which PDE4(A, B, C, and D), PDE7(A and B), and PDE8 (A and B) have high specificity for cAMP [ 10 , 11 ]. PDE3(A and B) and PDE4 are the two major cAMP-hydrolyzing enzymes [ 12 ].…”
Section: Introductionmentioning
confidence: 99%